Strategi Cyber Public Relations Polres Kabupaten Sumedang Dalam Meningkatkan Citra - Rizkiana, Ghina; Muhtadi, Asep Saeful; Fakhruroji, Mochamad (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to find out more about the cyber public relations strategy of the Sumedang District Police through Instagram in an effort to increase a positive image. The research method used is descriptive qualitative analysis. The concept used is Four Steps Public Relations from Cutlip, Center and Broom. The results of this study indicate that the Public Relations of the Sumedang District Police in the Cyber Public Relations strategy through Instagram social media in an effort to increase the positive image is carried out in several stages, namely: 1. The fact finding stage by means of field observations and informal research, 2. The planning stage by setting goals, targets, and content packaging strategies, 3. Action and communication stage by selecting information, content design, posting schedule and two-way communication, 4. Evaluation stage through measuring follower response data and regular meetings.